Learning moral values through cartoons for Malaysian preschool-aged children - Abdullah, Muhammad Alif Redzuan (Society for Research and Knowledge Management, 2023)
While the younger generation’s access to YouTube and time spent in front of the TV have increased, research on the ability of young children to learn moral values remains lacking. Furthermore, the preconceived notion that cartoons are detrimental to moral development is inconclusive, which requires further research to be confirmed or debunked. This study, which is mixed method research, aims to identify and analyse how moral values are taught in cartoons. A total of 20 preschool children (aged five to six years old) from an elementary school in Kuala Lumpur were selected. Doraemon animated series or movies were used as the study data. Notably, Doraemon animations and movies are popular among children as they are humorous and condemn bullying. This was followed by the process of data collection that comprised three phases. Specifically, the first phase was participant observation, the second phase was questionnaires, and the third phase was the unstructured interview. A statistical programme was conducted to analyse all the quantitative data collected from the surveys. Qualitative analysis software was used to analyse and code the qualitative data collected from observations and unstructured interviews. As a result, the majority of preschool children were in the imitation phase. Therefore, they imitated the good moral values portrayed in the cartoons they watched. This study also highlighted that preschool children's viewing of cartoons is not only entertaining but also educational and teaches important key moral values. Apart from that, the children preferred to watch cartoons rather than playing outside during their free time. The families' explanations helped the preschoolers distinguish between good and bad moral values in line with Malay culture and Islamic teachings. The analysis was limited by the small sample size and geographical location of this study. Thus, it was suggested that further studies are conducted to expand the economic strata and age groups.